Exploration of Moraceae Species in the Forest of Lemor Botanical Gardens, Suela District, Lombok Island, Indonesia - Dewi, Ariana Ashri; Raksun, Ahmad; Mertha, I Gde; Zulkifli, Lalu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Forest of Lemor Botanical Gardens in Suela District, Lombok Island, Indonesia, is known for its rich plant diversity, including members of the Moraceae family, which have important ecological and economic values. Existing records of Moraceae in this area are primarily based on botanical collections from the ex-situ zone, whereas information on species occurring in the in-situ forest conservation area remains limited. Therefore, this study was conducted to explore and identify species of the Moraceae family present in the forest area of Lemor Botanical Gardens. The research applied a descriptive exploratory approach using purposive sampling and the cruise method during field surveys conducted from September to November 2025. Data collection included counting individual plants, photographic documentation, morphological description, and voucher specimen verification. The study recorded sixteen species belonging to four genera in the Moraceae family, namely Ficus, Artocarpus, Streblus, and Morus, with a total of 805 individuals. Among these, Ficus septica was the most abundant species, with 125 individuals recorded, making it the dominant species in this habitat. These findings provide preliminary baseline data that can support conservation management of the area, complement the need for in-situ data, and document Moraceae botanical collections that had not previously been recorded within the ex-situ area of the botanical garden. In addition, the results are expected to serve as a scientific reference and to improve public understanding of Moraceae diversity.